Review of the tribe Smicromyrmini Bischoff, 1920 (Hymenoptera: Mutillidae) - Lelej, Arkady S.; Williams, Kevin A. (Zootaxa, 2023)
Twenty-six genera and five subgenera of the tribe Smicromyrmini are reviewed. The tribe (528 valid species) is Afrotropical (15 genera /126 species), Palaearctic (13/213) and Oriental (14/204) in distribution. The females are known for 80%, and males for 87%, of the 26 genera and five subgenera. The hitherto unknown female of Rasnitsynitilla Lelej in Lelej & van Harten, 2006 is described. New combinations are proposed for Rasnitsynitilla bartolozzii (Lo Cascio et Grita, 2014), comb. nov. (from the genus Smicromyrme Thomson, 1870) and Skorikovia sanguinicollis (Klug, 1829), comb. nov. (from the genus Ephutomma Ashmead, 1899). The genus Indratilla Lelej, 1993 is newly recorded from India and the subgenus Eremotilla Lelej, 1985 from the Oriental Region. Keys to females and males of these genera and subgenera of Smicromyrmini are provided. Habitus photos of males and/or females are provided for each genus and subgenus.